Factors Associated with the Utilization of Health Examinations in the Chronic Disease Management Program (PROLANIS) at the Primary Clinic of the Health Service Unit, Ministry of Health of the Republic of Indonesia - Fissilmi Kaaffah; Dwi Nurmawaty; Anggun Nabila; Ira Marti Ayu (Sean Institute, 2026)
Non-communicable diseases such as hypertension and diabetes mellitus remain major global health challenges. The World Health Organization reported that these diseases contributed to 43 million deaths (75% of global deaths) in 2021, with 18 million deaths occurring before the age of 70. In Indonesia, the number of chronic disease cases increased by 11% in 2024, from 29.7 million to 33 million cases. To address this issue, the government implemented the Chronic Disease Management Program (Prolanis) through BPJS Kesehatan to improve disease control, prevent complications, and enhance patients’ quality of life. However, preliminary findings at the Primary Clinic of the Health Service Unit, Ministry of Health of the Republic of Indonesia indicated that Prolanis utilization was still relatively low. This study aimed to identify factors associated with the utilization of Prolanis health examinations. A quantitative cross-sectional design was used with a sample of 68 respondents selected through purposive sampling. Data were collected between December 2025 and January 2026 and analyzed using univariate and bivariate analyses with the Chi-square test. The results showed that only 38.2% of respondents utilized Prolanis services. Knowledge was significantly associated with utilization (p = 0.005), while motivation, residential distance, and family support were not significantly associated with the utilization of Prolanis health examinations.